Physical and Chemical Interactions in Coal Flotation - Polat, Mehmet; Polat, Hürriyet; Polat, Mehmet; Chander, Subhash; Polat, Hürriyet (Elsevier Ltd., 2003)
Coal flotation is a complex process involving several phases (particles, oil droplets and air bubbles). These phases simultaneously interact with each other and with other species such as the molecules of a promoting reagent and dissolved ions in water. The physical and chemical interactions determine the outcome of the flotation process. Physical and chemical interactions between fine coal particles could lead to aggregation, especially for high rank coals. Non-selective particle aggregation could be said to be the main reason for the selectivity problems in coal flotation. It should be addressed by physical (conditioning) or chemical (promoters) pretreatment before or during flotation. Although the interactions between the oil droplets and coal particles are actually favored, stabilization of the oil droplets by small amounts of fine hydrophobic particles may lead to a decrease in selectivity and an increase in oil consumption. These problems could be remedied by use of promoters that modify the coal surface for suitable particle-particle, droplet-particle and particle-bubble contact while emulsifying the oil droplets. The role of promoters may be different for different types of coals, however. They could be employed as modifiers to increase the hydrophobicity of low rank coals whereas their main role might be emulsification and aggregation control for high rank coals. In this paper, a detailed description of the various phases in coal flotation, their physical and chemical interactions with each other in the flotation pulp, the major parameters that affect these interactions and how these interactions, in turn, influence the flotation process are discussed.
Keywords: High energy physics; Coal flotation; Aggregation; Molecules